Perspectives on diverse student identities in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Emerald Publishing Limited, 2018)
Higher education institutions continue to address an increasingly complex set of issues regarding equity, diversity and inclusion. Many institutions face increasing pressure to find innovative solutions to eliminate access, participation, and achievement barriers as well as practices that impede retention and graduation rates in higher education. This book provides educators with a global understanding of the challenges associated with the growing diversity of student identities in higher education and provides evidence-based strategies for addressing the challenges associated with implementing equity and inclusion at different higher education institutions around the world.
Prelims -- introduction to perspectives on diverse student identities in higher education -- Chapter 1: Accessibility and acceptance for university students with diverse abilities -- Chapter 2: Assisting student veterans with hidden wounds: evaluating student support in US higher education -- Chapter 3: The United States military veteran: a look at their college experience and equitable and inclusionary practices -- Chapter 4: "They say they value diversity, but I don't see it": academic and social experiences of first generation Latinx students at a predominately white Midwest institution -- Chapter 5: The influence of socioeconomic status on perceptions of persistence among African American students at major US universities -- Chapter 6: Eyes theory: a proposed racialization and developmental identity model for understanding concepts of race for international students of color studying in US higher education institutions -- Chapter 7: Failure can lead to success when remediation builds resiliency: how struggling international medical students gain entry into us graduate medical education programs -- Chapter 8: The end of lifelong learning - where have all the mature undergraduate students gone? A literature review and practical recommendations from a case study in England -- Chapter 9: From planning to realization: who goes? Who stops? What matters? -- About the authors Name index -- Subject index.
Includes indexes.
Print version record
Keywords: Educational equalization; Belonging (Social psychology); Minority students -- Education (Higher); Minority students -- Ethnic identity; Education -- Higher; Higher & further education, tertiary education